El dominio paramilitar y el Carnaval de Negros y Blancos en La Hormiga-Putumayo : campo simbólico en disputa (2020)
This research focuses on analyzing the process of the origin of the Carnival of Blacks and Whites that takes place in La Hormiga-Putumayo, as well as its trajectory and its subsequent consolidation as a festival in the territory. In this way, the research work was proposed to examine and investigate the significant experiences of some families from Nariño who decided to migrate, and the possible changes in cultural practices and the redefinition of the territory with the passing of time in the new place. On the other hand, we will approach the social dynamics and the implications that the war context has had in the Carnival dimension, with the configuration and resignification of the representations, one of the many forms that the war in Colombia has taken is evident: the control and dispute of various cultural manifestations by the armed groups, in our specific case during the paramilitary rule (1999-2006) in this area of the country.